Stability region derived by center of mass for older adults during trivial movements. (August 2021) - Liang, Shengyun; Zhao, Guoru; Zhang, Yu; Diao, Yanan; Li, Guanglin
Highlights: We have characterized age-related differences using RoS derived by CoM v and CoM a . The kinematic and kinetic data of complex movement were collected synchronically. The CoM ̃ v and CoM ̃ a demonstrated significantly different between old and young group. Time-independent RoS may be a benchmark for potentially predicting elderly fall. Abstract: Background: It is important to understand the dynamic stability mechanisms of the elderly in performing different body movements, as it may be related to fall prevention. Research question: How construct time-independent region of stability as bench-marked for elderly people during trivial movements? Methods: In this paper, we propose to construct time-independent region of stability (RoS) and characterize age-related differences using center of mass velocity ( CoM v ) and acceleration ( CoM a ) synchronically during left stand, right stand, left kick, right kick, walk, sit-to-stand. Twenty-nine subjects participated in the experiments. Six Vicon MX motion capture cameras and two AMTI OR6 Series Force Plate recorded the movements of elderly and young people. Statistical analyses and derivation formulas of RoS were proposed. Results: The normalized CoM v and CoM a for elderly group was found to be significantly difference to the young group when doing left stand, right kick, left kick. In addition, the normalized CoM a of elderly group demonstrated significantly larger than that of young group for left stand (−0.310 ± 0.142; −0.484 ± 0.186), right kick (−0.347 ± 0.118; −0.473 ± 0.161), walk (−0.388 ± 0.086; −0.433 ± 0.108). However, the normalized CoM a of elderly group demonstrated significantly smaller than young group for right stand (0.373 ± 0.166; 0.490 ± 0.197), left kick (0.365 ± 0.140; 0.466 ± 0.185), sit-to-stand (0.297 ± 0.151; 0.326 ± 0.148), that suggesting age-related differences in momentum control. Significance: The velocity and acceleration of CoM could provide a better understanding of human momentum control, which would better reveal the underlying mechanism of body instability and gait imbalance.